Análise da variação da taxa de internações hospitalares para tratamento de edema, proteinúria e transtornos hipertensivos na gravidez, parto e puerpério antes e durante a pandemia de Covid-19 em todas as regiões do Brasil - Giovanoni, Gabriela Vitória; Lopes, Eduarda Mendes; de Oliveira, Bruno Bibiano; Picolli, Bruno Edgar; de Araújo, Sarah Tairine Machado; Spagnol, Isadora Barreta; Dos Anjos, Ana Paula Backes; Rauber, Rafael; Kannenberg, Victória Pacheco; Lazzari, Fabiola Zancan; Loss, Vitoria; Pavan, Marcela Scussel (Brazilian Journal of Implantology and Health Sciences, 2024)
Pregnancy-induced hypertension is characterized by some diseases, such as gestational hypertension, pre-eclampsia (hypertension with proteinuria) and eclampsia (pre-eclampsia with seizures). Hypertensive diseases during pregnancy are responsible for high rates of maternal and perinatal morbidity and mortality, becoming one of the main public health problems. This work aimed to identify the prevalence of high blood pressure and its respective factors in pregnancy, childbirth and the postpartum period, and to verify the relationship between the number of cases and the Covid-19 pandemic. Quantitative observational study format with a demographic approach, carried out by collecting information from the database of the Ministry of Health - SUS Hospital Information System (SIH/SUS).